Good optical limiting performance of indium and gallium phthalocyanines in a solution and co-polymer host - Yuksek, Mustafa; Elmali, Ayhan; Durmuş, Mahmut; Yaglioglu, H. Gul; Unver, Hueseyin; Nyokong, Tebello (Iop Publishing Ltd, 2010)
The optical limiting characteristics of tetra- and octasubstituted gallium and indium phthalocyanine complexes have been studied by means of the open-aperture Z-scan technique with nanosecond pulses at 532 nm. The nonlinear response demonstrated that all investigated compounds exhibited strong reverse saturable absorption for both solution and solid-state-based experiments. The results showed that the ratio of the excited to ground state absorption cross section kappa and effective nonlinear absorption coefficient beta(eff) are largely dependent on the linear absorption coefficient. All compounds in chloroform exhibited almost the same optical limiting performance at the same linear absorption coefficient. Pc/PMMA composite films display a much larger effective nonlinear absorption coefficient, lower ratio of the excited to ground state absorption cross section and lower saturation fluence for optical limiting when compared to the same Pc molecules in solution. All gallium and indium complexes of phthalocyanines are good candidates for optical limiting applications.
Keywords: Z-scan; nonlinear absorption; optical limiting; polymer film; phthalocyanine